Development of a Maintenance System for Low Voltage Electricity Distribution Networks - Deitje S. Pongoh; Samsu Tuwokesong; Toban Pairunan; Milano. S. C. Manueke; Hazzel. Y. Ponglimbong; Brevandes. G. Moningka; Ceysi. J. I. Manumpil; Kristian. F. Angwarmase; Dandy. Y. Rory (Ravine Publisher, 2025)
This research focuses on important efforts to ensure the availability and reliability of electricity supply through the design and implementation of effective systems for monitoring and maintaining low voltage electricity distribution networks. The methods used in this research include analysis of maintenance needs, development of software for network monitoring, and integration of sensor technology for early detection of disturbances. The developed system aims to increase maintenance efficiency by providing real-time information about network conditions, enabling preventive action before disruptions occur. In addition, this system is also designed to reduce downtime and maintenance costs, as well as increase the reliability of electricity supply for customers. The research results show that implementing advanced sensor technology and monitoring software can significantly improve response to disruptions and minimize the impact on customer service. Thus, this system not only increases operational efficiency but also provides long-term benefits in maintaining the stability and reliability of electricity supply.